Two new Brazilian species of Neapion Alonso-Zarazaga, 1990 subgenus Neotropion Alonso-Zarazaga, 1990 with a key to South American species (Brentidae: Apioninae) - de Sousa, Wesley Oliveira; Ribeiro-Costa, Cibele Stramare (Zootaxa, 2018)
Two new Brazilian species of the genus Neapion Alonso-Zarazaga, 1990 subgenus Neotropion Alonso-Zarazaga, 1990 (Brentidae: Apioninae) are described and illustrated: Neapion (Neotropion) marquesae sp. n. (Type locality: Brazil, Mato Grosso) and Neapion (Neotropion) diringsi sp. n. (Type locality: Brazil, Amazonas). Neapion (Neotropion) marquesae sp. n. has dense, thin vestiture and raised areas on the elytra (recorded for the first time to the South American Apioninae); Neapion (Neotropion) diringsi sp. n. differs by the sparse vestiture and absence of raised areas. In addition to these characters, the vestiture color pattern and male genitalia characters such as the form of penis, length of the ‘tuning-fork’ shaped sclerite in the internal sac (the largest found in Apioninae) and the form of the tegminal plate are fundamental for the diagnosis of species of this subgenus. We also provide a key to the species of South American Neapion (Neotropion).